2004
DOI: 10.2105/ajph.94.4.646
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Case–Control Study Evaluating the Effectiveness of Speed Humps in Reducing Child Pedestrian Injuries

Abstract: Our findings suggest that speed humps make children's living environments safer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
2
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 17 publications
1
79
2
3
Order By: Relevance
“…58 Traffic calming devices were positively associated with collisions, whereas other studies revealed a negative association; however, no adjustment was made previously for traffic exposure. 49,59,60 Finally, the presence of school crossing guards was positively associated with collisions, which has similarly been found in Montreal, Quebec. 61 Features considered to be confounders in this analysis may fall on the casual pathway (particularly school crossing guards) between walking to school and pedestrian collisions.…”
Section: Comparisons Of Findings To Previous Studiessupporting
confidence: 65%
See 1 more Smart Citation
“…58 Traffic calming devices were positively associated with collisions, whereas other studies revealed a negative association; however, no adjustment was made previously for traffic exposure. 49,59,60 Finally, the presence of school crossing guards was positively associated with collisions, which has similarly been found in Montreal, Quebec. 61 Features considered to be confounders in this analysis may fall on the casual pathway (particularly school crossing guards) between walking to school and pedestrian collisions.…”
Section: Comparisons Of Findings To Previous Studiessupporting
confidence: 65%
“…43 Traffic calming has been associated with a 37% reduction in fatal pedestrian outcomes 48 and a 53% reduction in child pedestrian collision risk. 49 The BE influences both the walking exposure and risk, so it must be considered as a confounder in child pedestrian safety studies.…”
Section: Comparisons Of Findings To Previous Studiesmentioning
confidence: 99%
“…After the implementation of these measures, individual behavior will matter much less. 8,27 Traffic calming and improvement measures, which combine changes in traffic engineering, intense signage, barriers, restricted vehicle access, detours, and pedestrian refuge islands, may help reduce vehicle speed and increase drivers attention. [27][28][29][30] Traffic calming measures can reduce lethal and nonlethal injuries by around 11%.…”
Section: Pedestrian Safetymentioning
confidence: 99%
“…8,27 Traffic calming and improvement measures, which combine changes in traffic engineering, intense signage, barriers, restricted vehicle access, detours, and pedestrian refuge islands, may help reduce vehicle speed and increase drivers attention. [27][28][29][30] Traffic calming measures can reduce lethal and nonlethal injuries by around 11%. 30 Residential neighborhoods where families have many children and where there are many vehicles parked on the street and a large number of pedestrians are a priority for vehicle-pedestrian collision reduction programs.…”
Section: Pedestrian Safetymentioning
confidence: 99%
See 1 more Smart Citation